The US corporate income tax reform and its implications for the EU - Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2019)
The recent US tax reform, Tax Cuts and Jobs Act of 2017, lowered the statutory corporate income tax rates and brought other important changes for the taxation of multinational enterprises worldwide. This paper reviews these changes and discusses their effects for effective tax rates and tax revenues within the US as well as the EU. In the light of the uncertain impacts of the US reform, the EU doing nothing specific seems a reasonable response in the short term. Still, the EU should consider implementing policy proposals, which are good in themselves and regardless of the ultimate effects of the US reform. These include the Common Consolidated Corporate Tax Base and other measures focused at lowering the adverse effects of profit shifting to other countries as well as within the EU.
Keywords: F23; H25; P11; 330; policy reform; tax policy; Tax Cuts and Jobs Act of 2017; European Union; United States